Interventricular-Septal Output While Supported on Left Ventricular Assist Device Therapy. Issue 5 (7th November 2022) - Inglis, Sara S.; Villavicencio, Mauricio T.; Spencer, Philip J.; Schettle, Sarah D.; Stulak, John M.; Clavell, Alfredo L.; Kushwaha, Sudhir S.; Behfar, Atta; Rosenbaum, Andrew N.
Abstract : The effects of left ventricular unloading on septal function in patients with left ventricular assist devices (LVADs) have not been well characterized in vivo. The purpose of this study was to evaluate the relationship between markers of septal function with echocardiography in relationship to RV dysfunction and late RV failure after LVAD implantation. A retrospective study was conducted of patients supported on centrifugal-flow LVADs implanted over a 10-year period. Echocardiographic data were collected pre-operatively and up to 2 years after implantation. Interventricular septum (IVS) measurements were taken at end-systole and end-diastole. Interventricular-septal output (ISO) was calculated using the formula: (IVSs–IVSd)×heart rate. A total of 110 patients were included. An immediate and sustained reduction in both lateral annulus systolic velocity (RVS') and TAPSE were observed after implant ( p < 0.0001). However, ISO gradually decreased over time ( p < 0.0001). While ISO was not predictive of late RV failure, a decrease in ISO by 25% or greater from pre-implant to hospital discharge was associated with late RV failure (OR 4.8; 95% CI, 1.4–16.5; p = 0.012) even after adjusting for relevant clinical variables ( p ≤ 0.01 for each model). RV function is known to be influenced by mechanical ventricular interdependence and we demonstrate that measurement of ISO may be a useful marker in assessing RV dysfunction and predicting RV failure in patients following LVAD implantation.